"That's not something I was, I am, or am ever going to be:" multimodal self-assertion in digital video production. (March 2015) - Doerr-Stevens, Candance
Issues of representation and identity are paramount in youth media. These issues are further complicated when youth draw on popular culture and other media resources as vehicles to interpret and represent themselves (Alvermann, 2008, Jenkins et al., 2006 ). While youth-produced media often draw on popular culture resources and are frequently accused of reproducing dominant stereotypes, many young media makers are often acutely aware of their audiences and deliberately use media resources to establish social connections that will enhance and manipulate audience reception. Using mediated discourse analysis (Norris & Jones, 2005 ), this paper examines the documentary video production process of one such group of youth, exploring their process of purposeful selection and assemblage of popular culture and media resources. Findings reveal nuanced patterns of multimodal combination to establish and maintain attention of key audiences while asserting alternative social positions.